Artificial Intelligence in Higher Education and Scientific Research Future Development - Roumate, Fatima (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book explains the interaction between artificial intelligence and higher education. It explores artificial intelligence's tangible and intangible impact on higher education and scientific research and discusses how higher education and scientific research enhance the progress of artificial intelligence technologies. Based on systematic analysis with a multidisciplinary approach and a combination of theory and practice, the book brings original perspectives from the massive use of artificial intelligence in higher education and scientific research since the appearance of COVID-19. This book also discusses ethics in artificial intelligence, taking into consideration the recommendation on ethics of artificial intelligence adopted by UNESCO. This book explains the importance of technological sovereignty and new strategies to face current and future challenges related to e-learning, deep learning, and machine learning.
Preface -- Introduction -- Chapter 1. Artificial intelligence and scientific research: values at stake in education -- Chapter 2. Artificial intelligence and higher education legal limits -- Chapter 3. Artificial intelligence and the changing roles in the field of higher education and scientific research -- Chapter 4. Traditional and virtual universities: a rise of hybrid system -- Chapter 5. Virtual internationalization at universities: opportunities and challenges -- Chapter 6. Transformations of the scientific and technological revolution and the role of ai for education systems in the sustainable development paradigm -- Chapter 7. Challenges of university communication teaching in the artificial intelligence age -- Chapter 8. Educational Sovereignty and Artificial Intelligence Challenges: The Case of Morocco -- Chapter 9. Neurohacking and Artificial Intelligence in the vulnerability of the human brain: Are we facing a threat? -- Chapter 10. Ethics of artificial intelligence, higher education, and scientific research.
Keywords: Educational technology; Education, Higher; Artificial intelligence; Digital Education and Educational Technology; Higher Education; Artificial Intelligence